TEMPORAL CHANGES OF LAND SUITABILITY DATA FOR WHEAT CULTIVATION IN IRRIGATED REGIONS- MIDDLE OF IRAQ - & et al., MUHAIMEED (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
Al shehemia project in Wasit Governorate was selected to represent the Irrigated area in middle Iraq to study the temporal change in land suitability for wheat cultivation. Soils of the study area consist mainly, of ntisols and Aridisols soil orders .Historical Soil data were collected from previous works done in 1972 . and some soil propertic were reavoluoted at 2014. Soil and climate were evaluated for wheat cultivation according to Sys ,et al system (1993) and FAO, (1976) which developed by the Italian institute in 2012. The results showed that most of soil units are highly suitable for wheat growing with class S1 and consists about %85.34 from the total area, and %10.90 for N1and N2 classes. Land suitability for wheat cultivation increased to 92.37% for class S1 in 2014 due to the decrease in soil salinity. The results indicated that all soil units are affected by low organic carbon and this was affected on Suitability degree. The results indicated that suitability improved from 1972 to 2014 due to the decrease in soil salinity content resulted from praper management techniques that helped to leached the salts from the soils. The results showed that climate suitability for Wheat was highly Suitable (S1) for growing wheat in the study area during study period.